Emergence of ferrromagnetism in vanadium doped aluminium phosphide using density functional theory. (2020) - Kaur, Sharnjeet; Kaur, Kirandish; Sharma, Suresh; Rani, Anita
Abstract: The theoretical investigation of the structural, electronic and magnetic properties of Al0.75 V0.25 P Diluted Magnetic Semiconductors in Zinc Blende (B3) phase has been done using Density Functional Theory (DFT) as implemented in the Spanish Initiative for Electronic Simulations with Thousands of Atoms code using LDA + U as exchange–correlation (XC) potential. The study of electronic structures and magnetic properties show that doping of Vanadium transition metal atom in AlP results into induction of ferromagnetism with 100% spin polarization and develops half metallic character in Al0.75 V0.25 P ternary alloy. The calculated results of lattice constant, energy band gap and bulk modulus of pure AlP are in agreement with previous results available in literature. The calculated values of band gap and total spin polarization of Al0.75 V0.25 P are 1.816 eV and 2.0 μB respectively.